China-Indonesia Belt and Road Initiative: Changes in Political and Economic Drives - Putra, Husni Amriyanto (International Journal of Psychosocial Rehabilitation, 2020)
China has recorded groundbreaking economic successes in recent times which strengthened its position on the global stage and reinforced its audacity to dare new challenges and try new things. This moved it to unveil other ambitious projects which, if realised in compliance with its broader dream, will make it one of the biggest beneficiaries of globalization and reward its economy so bountifully that its power and influence will reach even remote parts of different continents. One of the unveiled projects is the One Belt One Road Initiative which aims at connecting friendly countries across the globe through a vibrant network of roads, rails and seaports to foster trade, integration and facilitate dealings among them especially in areas of shared interests. Indonesia is a major partner of the initiative and Chinese companies are investing heavily in different sectors in the country. We take a closer look at what is going on between the two countries in the context of BRI and analyse the project focusing on its aims and implications on the economic and political life of Indonesia and the rest of South-East Asia. We also cast an eye at agreements made within the framework of the initiative and end with the efforts of China and Indonesia to pursue a mutually beneficial relations.